De-signing design cartographies of theory and practice - Grierson, Elizabeth; Edquist, Harriet; Frichot, Hélène; Silverman, Hugh J. (Textures: Philosophy / Literature / Culture, 2015)
Throws new light on the terrain between theory and practice in transdisciplinary discourses of design and art. The editors bring together diverse approaches to design theory, practice, and philosophy from leading scholars in Australia, New Zealand, Japan, and the United Kingdom.